Agreement between the Clinical and Autopsy Results of Children Who Died with Pneumonia in Pediatric Intensive Care - Vásquez-Hoyos, Pablo; Bernal-Peña, Laura C.; Castro-Gómez, Daniel A.; Jaramillo, Lina; Polo, José F.; Parra-Medina, Rafael (Journal of Pediatric Intensive Care, 2020)
This study aimed to measure the agreement between the clinical and anatomopathological results of children who died with pneumonia from two pediatric intensive care units. Pediatric patients chosen were those who died between January 2008 and December 2015. The agreement was tested with Kappa. A total of 111 autopsies were included. Upon autopsy, 58 had pneumonia, 33 had it clinically and pathologically, 24 only clinically, and one only in autopsy. The Kappa agreement was 0.5 (95% confidence interval of 0.4 to 0.7). The level of agreement between the clinic and the autopsy is moderate. However, the consistency in cases of clinical pneumonia is low.
Keywords: pneumonia; autopsy; mortality; critical care; pediatrics